Unaltered responses of distal motor neurons to non-targeted thoracic spinal cord stimulation in chronic pain patients - Riera, Carolyn; de Oliveira, Daniela Souza; Borutta, Matthias; Regensburger, Martin; Zhao, Yining; Brenner, Steffen; Del Vecchio, Alessandro; Kinfe, Thomas M. (Pain and therapy, 2024)
Spinal cord stimulation (SCS) represents an established interventional pain therapeutic; however, the SCS effects of SCS waveforms on motor neuron recruitment of the lower limbs of chronic pain patients remain largely unknown.
Gesehen am 24.03.2025